2016
DOI: 10.1016/j.foodhyd.2015.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pectin properties on lipid digestion under simulated gastrointestinal conditions: Comparison of citrus and banana passion fruit (Passiflora tripartita var. mollissima) pectins

Abstract: a b s t r a c tMedium methoxylated pectin (52% mol/mol, MMP) was isolated from banana passion fruit (Passiflora tripartita var. mollisima) by hot acidic extraction. The impact of MMP on lipid digestion was compared to that of commercial citrus pectins with high (71% mol/mol, HMP) and low (30% mol/mol, LMP) methoxylation degree. A static in vitro digestion model was used to elucidate the impact of pectin properties (methoxylation degree and molecular weight) on the gastrointestinal fate of emulsified lipids. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 49 publications
1
52
0
2
Order By: Relevance
“…It was reported that bile salts was able to disrupt the interfacial protein network at very low concentration (0.005 mg/mL) [20]. The higher resistance of GG against interfacial displacement was presumably attributed to its higher binding affinity with bile salts [1,33,[42][43][44][45]. This seemed to coincide with the lower values of FFA 30 and R (Fig.…”
Section: Effect Of Interfacial Layer On the Sequential Adsorption Of mentioning
confidence: 86%
“…It was reported that bile salts was able to disrupt the interfacial protein network at very low concentration (0.005 mg/mL) [20]. The higher resistance of GG against interfacial displacement was presumably attributed to its higher binding affinity with bile salts [1,33,[42][43][44][45]. This seemed to coincide with the lower values of FFA 30 and R (Fig.…”
Section: Effect Of Interfacial Layer On the Sequential Adsorption Of mentioning
confidence: 86%
“…The spectra were recorded from 4000 to 500 cm -1 at a resolution of 8 cm -1 , averaged from 128 scans. Characteristic bands of non-cellulosic materials were taken into consideration: 1730 cm -1 ketone/aldehyde C=O stretch for both hemicelluloses and pectins (Xu et al 2013;Espinal-Ruiz et al 2016), 1100 and 1017 cm -1 bands as the strongest peaks of pectic polysaccharides (Kačuráková et al 2000), and 1507 and 1436 cm -1 C=C stretch for the aromatic rings of lignin (Sun et al 2000;Alemdar and Sain 2008) were evaluated. Peak intensities were related to the band at around 2900 cm -1 (C-H stretching) used as internal standard since it practically does not change during various treatments (Łojewska et al 2005).…”
Section: Removal Of Non-cellulosic Materialsmentioning
confidence: 99%
“…The release and solubilization of health‐promoting vitamins and nutraceuticals within the gastrointestinal tract (GIT) often depends on hydrolysis of the lipid phase that they are originally solubilized within (Yao and others ; Mao and Miao ; McClements and others ). Dietary fibers have already been shown to interfere with lipid digestion in a number of studies (Gidley ; Meshulam and others ; Torcello‐Gomez and Foster ; Verrijssen and others ; Dhital and others ; Espinal‐Ruiz and others ; Gunness and others ), and may therefore be expected to alter the bioavailability of triacylglycerols and any hydrophobic bioactive components associated with them. Hence, it is useful to determine how different types of dietary fiber impact lipid digestion, and to establish the molecular and physicochemical mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%